Promoter Liability and Consumer Protection in Concert Cancellations: A Legal Analysis of the Dua Lipa Case - Meidina Aulia; Surahmad Surahmad (MASI Mandiri Edukasi, 2025)
The cancellation of music concerts raises important questions about the legal responsibility of promoters toward audiences as consumers. This study examines how promoters fulfill their obligations when a concert is canceled and how audiences experience additional losses beyond the ticket price, such as transportation and accommodation costs. Using a normative juridical method supported by empirical data from interviews with three affected audiences, this study analyzes the cancellation of Dua Lipa’s concert in Indonesia to assess the alignment between legal norms and actual practice. The findings indicate that audiences continue to incur uncompensated losses, despite receiving refunds, as existing regulations do not cover indirect damages. The novelty of this research lies in its focus on unilateral cancellations caused by the promoter’s failure to meet technical standards, rather than force majeure or ticketing fraud—an area that has been rarely addressed in prior studies. This research contributes to the development of Indonesian entertainment law by highlighting the need for a specific regulatory framework under the Ministry of Tourism and Creative Economy to govern technical standards, refund mechanisms, and promoter liability, thereby strengthening legal certainty and consumer protection.